The potential impact of financial portability measures on mortgage refinancing: Evidence from Chile. (October 2021) - Madeira, Carlos
Highlights: Financial Portability affects mortgage refinancing via pecuniary and cognitive costs. Portability Laws may change both borrower behavior and refinancing monetary gains. Refinancing is positively associated with financial education and liquidity needs. Welfare gains of the law increase substantially if cognitive costs are lowered. Refinancing at better rates can improve the consumption channel of monetary policy. Abstract: This study estimates the potential impact of a recent Financial Portability Law in Chile on the households' mortgage refinancing probability. I show that mortgage refinancing is positively associated with financial education, liquidity needs, plus the value and timing for optimal refinancing. A counterfactual exercise shows the new legislation can substantially increase the refinancing probability and bring welfare gains, especially if it lowers the cognitive costs of the process. The refinancing probability may increase from 18% to 21.1% and create a welfare gain of 202 USD per borrower if only the pecuniary cost channel of the law is accounted for. However, the refinancing probability and welfare gains may increase to 29.2% and 902 USD, respectively, if the law can also significantly reduce the cognitive-education costs of refinancing. Welfare gains are larger for higher income households and owners of top valued homes. The refinancing gains could also boost the potential impact of monetary policy on consumption.